FORMULASI UNDANG-UNDANG BADAN HUKUM PENDIDIKAN (Pencarian Bentuk dan Batasan Pengaturan) - Suhrizal Suhrizal (Jurnal Dinamika Hukum, 2010)
Constitution court of justice verdict Number 11-14-21-126 and 136/PUU-VII/2009 that read date 31 march 2010 then, has juridical implication very vast towards education system in indonesia. Those implication not only limit the act number 9 year 2009 concerning education corporate body,  but it implicated to vast towards higher education management as a whole. This article means to study the decision and trace the will of constitution court of justice in the form of “education corporate body” that constitutional.Keyword; constitution, education, justice verdict